2003
DOI: 10.1159/000072230
|View full text |Cite
|
Sign up to set email alerts
|

Vypro II<sup>®</sup> Mesh in Hernia Repair: Impact of Polyglactin on Long-Term Incorporation in Rats

Abstract: Background: To the Vypro II® mesh, a large-pore-sized multifilamentous polypropylene mesh for hernia repair, supplementary polyglactin 910 multifilaments were added to improve intraoperative handling. As it has been suggested that polyglactin induces fibroplastic reactions and wound complications, this study was designed to evaluate the long-term tissue reaction to polyglactin in the Vypro II mesh. Materials and Methods: Two mesh materials, the Vypro II composite mesh (PP + PG) and the pure polyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 13 publications
(18 reference statements)
1
25
1
1
Order By: Relevance
“…However, in both cases the mucosa was not involved. This result is in contrast to Rosch et al, 23 who observed differences in the inflammatory reactions to this two mesh types. In another investigation, no differences were reported between this two meshes with regard to inflammatory reactions.…”
Section: Discussioncontrasting
confidence: 98%
“…However, in both cases the mucosa was not involved. This result is in contrast to Rosch et al, 23 who observed differences in the inflammatory reactions to this two mesh types. In another investigation, no differences were reported between this two meshes with regard to inflammatory reactions.…”
Section: Discussioncontrasting
confidence: 98%
“…In contact with the suture surface, inflammatory cells transform to foreign body giant cells. The entire inflammatory infiltrate (inner granuloma) is sealed by a collagen-rich fibrotic capsule (outer granuloma) [3,4]. Impaired biocompatibility leads to extended foreign body response.…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a la formación de fibrosis por la colocación de material protésico, en otro estudio en ratas sobre la reparación de hernias con malla Vypro II®, se comprobó que inicialmente aumentaba la reacción fibrótica e inflamatoria; sin embargo, hacia el día 112 después de la implantación completa de la malla, la fibrosis desaparecía y era menos evidente que, incluso, en los experimentos de control ( 14).…”
Section: Discussionunclassified